The Institute of Statutory Share as a Form of Permissibility Limitation (Of aTestament Freedom) in Inheritance Law of Russia and a Number of Foreign Countries - Ruslan USHAKOV; Vladimir GAVRILOV (Communications of International Proceedings, 2021)
The article analyses the problems of civil law regulation of the institute of statutory share in inheritance in Russia and a number of foreign countries using comparative-legal method. The subject of the research is legal relationships arising due to defining grounds for awarding and the size of statutory share in inheritance. The aim of the research is systematization of doctrine development on the theme, its comparison with corresponding Russian and foreign practice and also formulizing own scientific position. During the research dialectical method, general scientific methods of analysis, analogy and also system method were being used, special juridical method, particularly, comparative approach were applied. As the result authors on the basis of the current Russian and foreign civil legislation analysis suggest ways of solving identified issues by amendment of the Civil Code 1994 of the Russian Federation. Particularly, it is proved that in order to protect the interests of forced heirs the current Russian inheritance legislation should be supplemented by the provision on necessity of appreciation of the level of a devise need of incapable heirs, firstly – incapable dependents, when deciding whether the size of statutory share should be reduced or its awarding should be refused. The practicability of formalizing the list of circumstances connected with the financial status of the forced heir that a court must take into consideration in deciding the question of reducing the size of statutory share or refusing its awarding is proved.
Keywords: Inheriting; statutory share; forced heir; the Civil Code of the Russian Federation; Inheritance (Provision for Family and Dependants) Act 1975.